Suspended at the Brink of Death: Encephalitis Lethargica and Allaying Public Fears, 1916-1926 - Caron, Simone M. (Advances in Social Sciences Research Journal, 2025)
This article examines the outbreak of encephalitis lethargica during the era of World War I. It analyzes the scientific discussions concerning encephalitis lethargica at the national level and provides a microanalysis of how newspapers and public health bulletins in Forsyth County, North Carolina, covered the topic. These sources of information kept the public informed about the latest scientific theories, outbreaks, and means to avoid the disease, and downplayed the severity of the disease to assure the alarmed public that there was no reason to panic despite the unknown etiology of encephalitis lethargica.